Fishing net waste management: quantification and valorization - Beate Zlaugotne; Jelena Pubule; Julija Gusca (Frontiers in Marine Science)
Abandoned, lost or discarded fishing gear harms marine ecosystems by releasing microplastic waste from synthetic materials, reducing biodiversity, spreading invasive species and causing long-term damage to fragile habitats. Therefore, it is essential to evaluate fishing gear waste quantities and establish efficient waste management strategies focused on reuse, recycling and recovery. This research develops a methodology to assess the quantity of discarded fishing nets and scrap waste from Latvia’s fishing gear industries, explores potential waste valorization scenarios and evaluates them based on the country-specific circular economy principles. The study employs environmental life cycle assessment (avoided burden approach) and environmental damage cost methods to evaluate different waste management scenarios for discarded fishing nets in Latvia. Findings show that manufacturing scraps exceed discarded fishing nets, with Latvia averaging 53 tons of fishing net waste annually from 2018 to 2023, and a notable drop in manufacturing during COVID-19. The assessment of valorization scenarios demonstrates that recycling fishing nets for nylon production and asphalt reinforcement significantly reduces both environmental impact and costs. Specifically, recycling for nylon production avoids 7850 kg of CO2 eq. and reduces environmental damage costs by 2947 Euro per tonne of discarded fishing nets. For asphalt reinforcement, it avoids 636 kg of CO2 eq. and results in a cost reduction of 407 Euro per tonne of discarded fishing nets. In contrast, the less environmentally feasible options, syngas production and landfilling, show higher environmental footprints. Syngas production generates 156 kg CO2 eq. per tonne of fishing nets and incurs an additional environmental damage cost of 31 Euro per tonne, but it is still a preferable alternative to landfilling. Landfilling has the most severe impact, generating 12100 kg CO2 eq. and costing 29609 Euro per tonne, making it the least favorable option and one that should be avoided. Research underscores the necessity for uniform data collection on fishing net waste and enhanced collaboration among stakeholders to facilitate valorization and investment efforts.